2012
DOI: 10.1016/j.jmb.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Myristoylated Mason-Pfizer Monkey Virus Matrix Protein and the Role of Phosphatidylinositol-(4,5)-Bisphosphate in Its Membrane Binding

Abstract: We determined the solution structure of myristoylated Mason-Pfizer monkey virus matrix protein by NMR spectroscopy. The myristoyl group is buried inside the protein and causes a slight reorientation of the helices. This reorientation leads to the creation of a binding site for phosphatidylinositols. The interaction between the matrix protein and phosphatidylinositols carrying C8 fatty acid chains was monitored by observation of concentration-dependent chemical shift changes of the affected amino acid residues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 43 publications
4
63
0
Order By: Relevance
“…PI(4,5)P 2 binds to HIV-2 MA in a manner that is essentially identical to that of HIV-1 MA; however, structural data revealed that the myr group in HIV-2 MA is tightly sequestered and does not exhibit concentration-or PI(4,5)P 2 -dependent exposure (61). Another recent study on Mason-Pfizer monkey virus MA also revealed that the myr group is tightly sequestered and that PI (4,5)P 2 binding to MA does not trigger myr exposure (62). The MA proteins of RSV and equine infectious anemia virus (EIAV) lack myr modification; Gag binding to the PM is mediated by electrostatic interactions (63)(64)(65).…”
Section: Discussionmentioning
confidence: 95%
“…PI(4,5)P 2 binds to HIV-2 MA in a manner that is essentially identical to that of HIV-1 MA; however, structural data revealed that the myr group in HIV-2 MA is tightly sequestered and does not exhibit concentration-or PI(4,5)P 2 -dependent exposure (61). Another recent study on Mason-Pfizer monkey virus MA also revealed that the myr group is tightly sequestered and that PI (4,5)P 2 binding to MA does not trigger myr exposure (62). The MA proteins of RSV and equine infectious anemia virus (EIAV) lack myr modification; Gag binding to the PM is mediated by electrostatic interactions (63)(64)(65).…”
Section: Discussionmentioning
confidence: 95%
“…For example, on the one hand, the specificity of the HIV-1 MA binding pocket for short-chain PI(4,5)P2 is well established (7), and depletion of PI(4,5)P2, the major PIP species at the PM, compromises HIV-1 Gag PM association (8,9,11). But on the other hand, HIV-1 Gag shows only very modest specificity for PI (4,5)P2 by flotation analysis (8,9). It remains to be established to what degree PIP stimulation of membrane binding in vitro is due only to electrostatics.…”
Section: Amentioning
confidence: 99%
“…Examples include human immunodeficiency virus type 1 (HIV-1) and HIV-2, Mason-Pfizer monkey virus (MPMV) (4), and EIAV (5). Other viruses, such as RSV, murine leukemia virus (MLV), and human T-lymphotropic virus (HTLV), apparently do not (6,7).…”
mentioning
confidence: 99%
“…Mutating these residues results in reduction of Gag membrane association and of virus release (5)(6)(7). In vitro, the negatively charged lipids phosphatidylserine (PS) or phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] are crucial for Gag or MA membrane association (8)(9)(10)(11)(12)(13). Second, the Gag proteins of most retroviruses, like HIV-1, are modified by addition of the 14-carbon fatty acid myristate at the N-terminal glycine residue.…”
mentioning
confidence: 99%